DEMOKRASI DAN MUSYAWARAH DALAM PANDANGAN DARUL ARQAM, NII, DAN HIZBUT TAHRIR INDONESIA - Asep Zaenal Ausop (Fakultas Seni Rupa dan Desain ITB, 2009)
Darul Arqam (DA), Negara Islam Indonesia (NII), and Hizbut Tahrir Indonesia (HTI) are the Islamic movement (harakah Islamiyah) which posses its own view on democration and deliberation, clearly distinctive from the view of common Indonesian and world people. Why they posses their own view, what is the argument behind, and what the experts say about these movement, this is matter that everybody must know. The goal of this research is to cover valid data and scientific facts about these three view of the Islamic organizations about democracy and deliberation, analyzed them, and compared with notions of other Islamic thinkers. This is a qualitative research with theological approach as methodological approach and explanatory descriptive as research method. The result of this research proofs that Darul Arqam (DA), Negara Islam Indonesia (NII), and Hizbut Tahrir Indonesia (HTI) posses same view that democracy is proscribe. For them, the truth that came from majority voters is an adversative to God's absolute dominance principle and change the God's authority as law maker, their argumentation is distinguishable each other though. Key word : demokrasi, musyawarah, khilafah, ahlul halli wal aqdi.